Digital Música Poética and Classical Spanish Theatre: a window to the world - Avilés, Rosa (Talía. Revista de estudios teatrales, 2021)
The present article addresses the interdisciplinary work of Digital Música Poética, a research project with a database that unites the poetic and musical heritage of Spanish Barroque theatre. Philologists and musicologists harmonically cooperate as both disciplines did in the 17th century, and contemporary innovative digital tools allow the user to access hyperlinks which open the door to an auditive universe that has remained silent up until now but which, undoubtedly, forms part of our cultural patrimony.